Decision Making Under Uncertainty Market During Covid-19 - Jafar, Rizka; Meilvidiri, Wayrohi (Journal of Developing Economies, 2022)
This article discussed decision-making models in the context of crisis and uncertainty during the COVID-19 pandemic. Time and information constraints, the effectiveness of government policies, and public expectations were used to build the research model. Data were collected by distributing a semi-open and closed survey questionnaire (Google Forms). The statistical result showed that the decisions taken during a crisis/pandemic were more determined by the time constraints and the information (significantly positive) than the government policies and the public expectations (negative is not significant). Related to the effectiveness of the health and economic policies taken by the government, it concluded the effective response; however the virus recurs, the public health response succeeds, but measures are insufficient to prevent recurrence so that physical distancing continues (regionally) for several months. Analysis of the survey respondents towards the government economic policy assessed that government policy was still partially effective intervention, policy responses partially offset economic damage, the banking crisis was avoided, and muted recovery levels. The economic impact of co-19 predicted a slow economic recovery, supported by respondents' expectation of pessimism towards future economic conditions.